PENGARUH PERENCANAAN, PENGAWASAN, DAN KOORDINASI TERHADAP EFEKTIVITAS SISTEM E–LAYANAN DI BADAN PENDAPATAN DAERAH KOTA SURAKARTA - Damayanti, Anissa Vika; Winarti, Winarti; Suranto, Joko (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The purpose of this study was to know the effect of planning, supervision and coordination on the effectiveness of the e-service system at at the Regional Revenue Agency Surakarta. This type of research uses a casual associative strategy through quantitative methods. This research is located at the Regional Revenue Agency of Surakarta City. The research population was 40 permanent employees with saturated sample technique. Data collection used a questionnaire. Data analysis techniques used multiple linear regression. The results showed that planning has a significant effect on the effectiveness of the E-Service system. Supervision has a significant effect on the effectiveness of the E-Service system. Coordination has a significant effect on the effectiveness of the E-Service system. Planning, supervision and coordination affect the effectiveness of the E-Service system simultaniously. Keywords: planning, supervision, coordination, effectiveness